Penerapan Metode Lean Six Sigma Dmaic Dalam Optimalisasi Overcapacity Gudang Chemical Plant Marunda PT Smart Tbk. - Novrianne, Gunaika Clarissa; Kirana, Made Nindya; Junius, Eldwin (Study Program of Industrial Engineering, Udayana University, 2025)
PT SMART Tbk is one of the largest palm oil processing companies in Indonesia. In its production process, the company uses various types of chemicals stored in a dedicated chemical warehouse. Data shows that the pallet capacity at the chemical warehouse in the Marunda Plant frequently reaches full capacity or even overcapacity, which poses a risk of disrupting production flow, such as delays in the movement of materials and accumulation of stock. This study aims to identify the types of waste that contribute to overcapacity and determine the root causes of the problem. The research is limited to the chemical warehouse at the Marunda Plant, focusing on inbound activities for flavor products (code VO16745) and outbound activities for ingredients (code Salt 300265). Based on the analysis using Process Activity Mapping and Value Stream Mapping, the waste level in warehouse operations was found to be 56%, with a total cycle time of 3,528 seconds and a value-added time of 1,536 seconds. This waste directly contributes to overcapacity and decreases warehouse efficiency. Using the Lean Six Sigma DMAIC approach, the root causes were identified through Fishbone Diagram and Root Cause Analysis. The main contributing factors include large vendor packing sizes and minimum order quantities (MOQ), increasing annual demand, limited manpower, narrow warehouse space, small unloading doors, narrow aisles, and a lack of pallets and shelves. As a solution, it is recommended to expand the warehouse area, add more operators, enlarge the unloading doors, and increase the number of pallets and shelves to optimize operations and reduce the risk of overcapacity.